SMART HOME TECHNOLOGY BASED OF INTERNET OF THINGS AS AN ACTIVITY SUPPORT IN THE HOME INTERIOR DESIGN IN THE DIGITAL ERA - maya, Ista Ratna (Ide dan Dialog Desain Indonesia (Idealog), 2021)
The number of human activities requires humans to be more productive. Nowadays, to support this, some human work has been assisted by digital technology, both office work, work done outside the room, or homework. The purpose of this research is to introduce to the public related to digital technology that is not widely known by the general public, especially Balinese people. This digital technology is called a Smart Home system based on the Internet of Things, a technology that can be applied to residential design. This system functions to assist the activities of residential users in various ways. This IoT-based Smart Home technology can be combined with several facilities in interior design such as lighting facilities, ventilation and complementary elements to form space. Iot allows users to manage most of these facilities through an application on a smart phone as long as the facility is connected to the internet. Key words : Smart Home, Internet of Things, Residential home